Inclusive b-jet production in pp collisions at root s=7 TeV - Chatrchyan, S. (2012)
The inclusive b-jet production cross section in pp collisions at a center-of-mass energy of 7TeV is measured using data collected by the CMS experiment at the LHC. The cross section is presented as a function of the jet transverse momentum in the range 18 < p(T) < 200 GeV for several rapidity intervals. The results are also given as the ratio of the b-jet production cross section to the inclusive jet production cross section. The measurement is performed with two different analyses, which differ in their trigger selection and b-jet identification: a jet analysis that selects events with a b jet using a sample corresponding to an integrated luminosity of 34 pb(-1), and a muon analysis requiring a b jet with a muon based on an integrated luminosity of 3 pb(-1). In both approaches the b jets are identified by requiring a secondary vertex. The results from the two methods are in agreement with each other and with next-to-leading order calculations, as well as with predictions based on the PYTHIA event generator.